Watery Eyes - Mahmood, Tahir (Pakistan Journal of Ophthalmology, 2006)
The word “Watering” from the eyes is one of the commonest word which an ophthalmologist hear every day, probably everywhere in the world. It is among the most common lacrimal symptoms. There is a long list of causes, which may be responsible for this, and patients of all ages are affected. One of two reasons; either they produce too many tears or the tears that are produced are not properly drained from the conjunctival sac. In order to find out the cause, where a through knowledge of the anatomy and pathophysiology is required, there a thorough history of the condition is essential to make the distinction between the two possible mechanisms. A clinician’s approach to lacrimal disorders should be logical and organized. Just as neurologic disorders must be carefully localized, so too should lacrimal problems be correctly localized and diagnosed before treatment is implemented. A thorough evaluation of the lacrimal drainage system should begin with the eyes, eyelids, and puncta and terminate with the distal nasolacrimal duct and intranasal passages. Haphazard trial-and-error therapies are to be avoided.